Implementing a decision support system in the transport process management of a small Slovak transport company - Miroslava Nyulásziová; Dana Paľová (Journal of Entrepreneurship, Management and Innovation)
It is indisputable that the continuous development of digital technologies influences the business environment. Using information technologies means easier access to a huge amount of business information, which is hard to include in day-to-day decision-making. Traditional data processing methods in business management become inadequate. So, business process management approaches and business data analysis are the tools that could be utilized to optimize processes in a company and to harvest valuable information that can provide a variety of decision-making material for company management. This article deals with the analysis, modeling, and optimization of the transport process, as well as the design of a system for decision support in this process within a small transport company. The research is focused on the development of an innovative decision support system based on a company’s data analysis in order to improve the management of the transport service process.